Internationalization of higher education institutions as one of the pedagogical conditions for the development of foreign language communicative culture of students - Malyk, Valentyna (Educational Challenges, 2025)
The article explores the importance of foreign language proficiency as a key factor in the internationalization of higher education. It examines the concept of “condition” from various perspectives, highlighting pedagogical conditions as a combination of content, methods, and resources that support educational goals. The role of foreign language communicative culture is emphasized as essential for university internationalization. The study also demonstrates that internationalization offers multiple benefits at different levels – including faculty, students, research, and academic programs.Purpose: The objective of the study is to analyze the current level of students’ foreign language communicative culture due to its importance as an effective pedagogical condition on the path to the internationalization of higher education.Methodology: The methodology covers a comprehensive set of theoretical and empirical research methods, including the analysis of scientific sources, regulatory documents, pedagogical observation, description, classification and systematization. The study was related to full-time students at Vinnytsia National Agrarian University.Results: The content of a foreign language communicative culture covers social, linguistic, regional, psychological and pedagogical aspects. Therefore, to form a foreign language communicative culture of an individual, it is necessary to gradually develop deep, systematic knowledge of a foreign language, assimilate universal human values and form appropriate behavioral algorithms.Conclusions: The use of a foreign language as a means of intercultural communication is a key factor in the formation of a foreign language communicative culture in the university. This approach contributes not only to the development of speech skills, but also ensures the cultivation of tolerance, an understanding of cultural differences and effective interaction in a globalized society. It also helps in the process of internationalization of universities.
Keywords: bilingualism; foreign language communicative culture; multilingual environment; professionally oriented vocabulary; term